2008
DOI: 10.1075/lic.8.1.04fen
|View full text |Cite
|
Sign up to set email alerts
|

L1 effects on the emergence of ESL sentence processing skills of Chinese and Korean ESL learners

Abstract: This study examines the emergence of lower-level ESL sentence processing skills involved in integrating English words into predicate structures on-line. The aim of the present study is to examine how the L1 phrase structure and corresponding L1 word integration skills of ESL learners influence their corresponding ESL sentence processing skills in an on-line English sentence reading task. The study examined the English predicate and verb phrase processing skills of a group of Chinese ESL learners whose language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Such late development of definition forms may be related to the typologically and syntactically very distinguished pair of languages that the Korean–English bilingual children were acquiring. In this respect, this particular finding also conforms to previous studies on the less readily made syntactic transfer of Korean English learners’ relative clauses in the two languages (Comrie, 2007; Fender, 2008). As construction of relative clauses in English is a late development for Korean English learners, possibly because of the linguistic differences between their L1 and L2 (Choi, 2007; Lee, 2005), producing word definitions that conform to the conventional Aristotelian form may have been challenging despite their awareness of conventional formal definitions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such late development of definition forms may be related to the typologically and syntactically very distinguished pair of languages that the Korean–English bilingual children were acquiring. In this respect, this particular finding also conforms to previous studies on the less readily made syntactic transfer of Korean English learners’ relative clauses in the two languages (Comrie, 2007; Fender, 2008). As construction of relative clauses in English is a late development for Korean English learners, possibly because of the linguistic differences between their L1 and L2 (Choi, 2007; Lee, 2005), producing word definitions that conform to the conventional Aristotelian form may have been challenging despite their awareness of conventional formal definitions.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it has been argued that language distance is an important source of such language transfer (Chan, 2004). In this respect, studies have identified L1 effects on L2 relative clause construction in relation to typological differences between the two languages (Comrie, 2007; Fender, 2008). While syntactic transfer of relative clause formation was easily identified among Chinese–English bilinguals (Chan, 2004; Yip & Matthews, 2000), “surprisingly little transfer” was observed in bilinguals acquiring two distant languages such as Japanese and Korean English learners (Comrie, 2007; Fender, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eender (2008), in the process of learning and mastering L2, the process of learning B2 does not occur directly to non-native speakers as they do not master all the skills in B2, such as mastering L1 and face great constraints as a result of the influence of L1. Corder (1981) is of the view that L2 learning begins after most of the child's maturation process is completed because it is part of the child's maturation process.…”
Section: Introductionmentioning
confidence: 99%